Including Indigenous Peoples in Geospatial Services - Moore, Thomas (Frontiers in Climate, 2022)
This article addresses the benefits and challenges to including indigenous peoples and their organizations as partners in the geospatial services provided by SERVIR-Amazonia, a USAID and NASA initiative implemented in six Amazon Basin countries. It discusses the significance and importance of Amazon peoples, their ancestral territories, and the benefits and importance to humanity of sharing and improving geospatial technology with them to help them defend and plan for the management and conservation of those territories. It describes the challenges of engaging and communicating with Amazon indigenous peoples, working through their organizations, and responding to their needs and priorities in a culturally sensitive manner and provides feedback to orient both geospatial services and environmental policy.